2015
DOI: 10.1371/journal.pcbi.1004420
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization in Balanced State Networks by STDP and Homeostatic Plasticity

Abstract: Structural inhomogeneities in synaptic efficacies have a strong impact on population response dynamics of cortical networks and are believed to play an important role in their functioning. However, little is known about how such inhomogeneities could evolve by means of synaptic plasticity. Here we present an adaptive model of a balanced neuronal network that combines two different types of plasticity, STDP and synaptic scaling. The plasticity rules yield both long-tailed distributions of synaptic weights and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
64
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 89 publications
(208 reference statements)
3
64
1
Order By: Relevance
“…389 A neuron with a high firing rate therefore has a higher probability of making its 390 outgoing weights larger, exploiting STDP to achieve a stronger influence on the network. 391 With the above, we replicate findings by Effenberger and colleagues ('driver 392 neurons', [19]), and extend them to inhibitory neurons. Moreover, the impact of a 393 neuron on the rest of the network should be a function of both its firing rate and its 394 outgoing weights (see Methods).…”
supporting
confidence: 82%
“…389 A neuron with a high firing rate therefore has a higher probability of making its 390 outgoing weights larger, exploiting STDP to achieve a stronger influence on the network. 391 With the above, we replicate findings by Effenberger and colleagues ('driver 392 neurons', [19]), and extend them to inhibitory neurons. Moreover, the impact of a 393 neuron on the rest of the network should be a function of both its firing rate and its 394 outgoing weights (see Methods).…”
supporting
confidence: 82%
“…23 Moreover, the discovered skeleton of neurons with strong bi-directional links may help 24 to optimize information storage [15]. 25 In a recent paper [16], we have investigated the relation between connectivity and 26 system dynamics in small motifs of probabilistic neurons with binary outputs, assuming 27 discrete, ternary connection strengths. We found that the balance between excitatory 28 and inhibitory connections has a strong effect on the transition probabilities between 29 successive motif states, whereas the total density of non-zero connections is less 30 important.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fine tuning of the balance 187 parameter can bring the system to the edge of the chaotic regime, where the outputs of 188 the neurons produce complex wave forms, and where the system may depend sensibly, 189 but still regularly, on external inputs. We speculate that this regime is most suitable for 190 purposes of neural information processing [20][21][22][23][24], and that biological brains may 191 therefore control the parameterb in a homeostatic way [1,25,26].…”
mentioning
confidence: 99%
“…Modularity, the presence of clusters of elements that are more densely connected witch each other than with 17 the rest of the network, is a ubiquitous topological feature of complex networks and, in particular, structural 18 brain networks at various scales of organization [1]. 19 Modularity was among the first topological features of complex networks to be associated with a systematic 20 impact on dynamical network processes. Random walks are trapped in modules [2], the synchronization of 21 coupled oscillators over time maps out the modular organization of a graph [3] and co-activation patterns of 22 excitable dynamics tend to reflect the graph's modular organization [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Given the well accepted role of synaptic plasticity in brain 39 development and activity-dependent adaptation [19], other perspectives focus on changes driven by such local 40 plasticity mechanisms in physiologically more realistic models. A considerable proportion of this work aims at 41 explaining empirically observed distributions of physiological parameters at the cellular scale, such as synaptic 42 weights [20], and only a few studies have paid attention to topological aspects, such as the proportion of local 43 motifs [21]. Some of the mentioned modeling studies showed an emergence of modular network structure and 44 attempted to provide an underlying mechanism based on the reinforcement of paths between highly correlated 45 nodes [22].…”
Section: Introductionmentioning
confidence: 99%